2020
DOI: 10.1186/s12891-020-03250-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimum 8-year follow-up of revision THA with severe femoral bone defects using extensively porous-coated stems and cortical strut allografts

Abstract: Background: Revision total hip arthroplasty (THA) with severe femoral bone defects remains a major challenge. The purpose of this study is to report the minimum 8-year clinical and radiographic results of revision THA with severe femoral bone defects treated with extensively porous-coated stems and cortical strut allografts. Methods: We retrospectively identified 44 patients diagnosed with Paprosky type III and IV femoral bone defects between January 2006 and July 2011. The exclusion criteria were patients not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…All struts achieved union with 10-year revision for any cause survivorship at 96.2% (95% CI: 75.7e99.5%). 31 Others have reported similar outcomes, Park et al reviewed their use of cortical strut allografts in 19 hip revision patients with 94.7% incorporation rate with average 21.2 months' time to union with no significant differences between patients with fractures, aseptic loosening or infection. 32 The role of strut allografts for managing patients with hip periprosthetic fractures around/or at the tip of well-fixed implants (Vancouver B1) continues to be debated in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…All struts achieved union with 10-year revision for any cause survivorship at 96.2% (95% CI: 75.7e99.5%). 31 Others have reported similar outcomes, Park et al reviewed their use of cortical strut allografts in 19 hip revision patients with 94.7% incorporation rate with average 21.2 months' time to union with no significant differences between patients with fractures, aseptic loosening or infection. 32 The role of strut allografts for managing patients with hip periprosthetic fractures around/or at the tip of well-fixed implants (Vancouver B1) continues to be debated in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, the clinical results showed that the improved mHHS and MSTS scores were similar to previous studies reported. 9,28,29 The radiologic outcomes showed all the allografts were united to the host bone at the latest follow-up. Therefore, we believed that the revision technique using cortical strut allografts was also suitable for benign bone tumors patients.…”
Section: Discussionmentioning
confidence: 96%
“…Adverse events were recorded at the latest follow‐up. Adverse events including aseptic loosening, periprosthetic joint infection, periprosthetic fracture, hip dislocation, blood transfusion, venous thrombosis, pulmonary embolism and neurovascular events, were collected in details 14,15 …”
Section: Methodsmentioning
confidence: 99%